DIPARE UNTUK MENSUKSESKAN PEMBELAJARAN DARING PADA MASA PANDEMI COVID 19 - SUHARNI SUHARNI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The background for the preparation of this scientific paper is an appeal from the government regarding the COVID-19 pandemic, so to break the chain of spread of COVID-19 learning is carried out online. To overcome the problems that arise in the implementation of online learning and to improve the quality of online learning, the principal of SD Negeri Plosojenar implements the DIPARE policy to make online learning successful during the COVID-19 pandemic. The objectives of this scientific paper are: 1) Describe the implementation of DIPARE for the success of online learning, 2) Describe the results or impacts of implementing DIPARE activities at SD Negeri Plosojenar, 3) Describe the follow-up to the development of DIPARE activities to make online learning successful at SD Negeri Plosojenar, Jakenan District Starch. The implementation of DIPARE activities (discussion, innovation, participation, accountability, reword, and evaluation) is carried out in an effort to accommodate the obstacles that occur in online learning, and involve all school members in overcoming the obstacles that arise. The role of all parties is expected to be able to overcome the obstacles that arise so that the quality of online learning can increase. The results of the implementation of DIPARE activities show that the participation of all school members is very helpful in improving the quality of online learning and increasing the professionalism of educators. From the results of these activities, teachers as educators gain experience and knowledge in implementing various applications that can be used for online learning so that learning can run well and is fun. ABSTRAKLatar belakang disusunnya karya ilmiah ini adalah adanya himbauan dari pemerintah terkait adanya pandemi COVID-19 maka untuk memutus mata rantai penyebaran COVID-19 pembelajaran dilakukan secara daring. Untuk mengatasi permasalahan-permasalahan yang muncul pada pelaksanaan pembelajaran daring dan untuk meningkatkan kualitas pembelajaran daring maka kepala sekolah SD Negeri Plosojenar menerapkan kebijakan DIPARE untuk mensukseskan pembelajaran daring pada masa pandemi COVID-19. Tujuan karya ilmiah ini adalah: 1) Memaparkan pelaksanaan DIPARE untuk mensukseskan pembelajaran daring, 2) Memaparkan hasil atau dampak dari pelaksanaan kegiatan DIPARE di SD Negeri Plosojenar, 3) Memaparkan tindak lanjut pengembangan kegiatan DIPARE untuk mensukseskan pembelajaran daring di SD Negeri Plosojenar Kecamatan Jakenan Kabupaten Pati. Pelaksanaan kegiatan DIPARE (diskusi, inovasi, partisipasi, akuntabel, reword, dan evaliasi) dilaksanakan dalam upaya menampung hambatan-hambatan yang terjadi dalam pembelajaran daring, serta melibatkan semua warga sekolah dalam mengatasi hambatan-hambatan yang muncul tersebut. Peran dari semua pihak diharapkan dapat mampu mengatasi hambatan-hambatan yang muncul sehingga kualitas pembelajaran daring dapat meningkat. Hasil dari pelaksanaan kegiatan DIPARE menunjukkan bahwa partisipasi dari semua warga sekolah sangat membantu dalam meningkatkan kualitas pembelajaran daring dan meningkatkan profesionalisme para pendidik. Dari hasil kegiatan tersebut guru sebagai pendidik mendapatkan pengalaman serta pengetahuan dalam menerapkan berbagai aplikasi yang dapat digunakan pembelajaran daring sehingga pembelajaran dapat berjalan dengan baik dan menyenangkan.